Troubleshooting in complete denture fabrication - N Sanjana Devi; Deepak Nallaswamy Veeraiyan; Subhabrata Maiti; Minal Tulsani; Divya Rupawat (Wolters Kluwer Medknow Publications, 2022)
In countries with a high amount of geriatric patients, it is mandatory for a dental clinician to have working knowledge on complete denture (CD) procedures. The aim of this study was to troubleshoot the errors in denture fabrication by assessing the difficulties in clinical procedures. A questionnaire was distributed among dental undergraduates across the country in the present study. A total of 26 questions were included in the study. An online sharing medium was used for distribution and a total of 140 responses were received. SPSS for windows, version 20 was used for data tabulation. Descriptive statistics and Chi-square test were done. The results of this study revealed that jaw relation was the most difficult procedure followed by border molding. Multiple problems arise from the practitioner's end due to the lack of knowledge. One of the causes for these problems could be inability to learn the principles and procedures during the undergraduate program. This must be addressed at the base level so that better care can be given to patients.